Climate Change, Inequality, and Human Migration - Michał Burzyńskia; Christoph Deuster; Frédéric Docquier; Jaime de Melo (Institute of Labor Economics (IZA), 2019)
This paper investigates the long-term implications of climate change on local, interregional, and international migration of workers. For nearly all of the world's countries, our micro-founded model jointly endogenizes the effects of changing temperature and sea level on income distribution and individual decisions about fertility, education, and mobility. Climate change intensifies poverty and income inequality creating favorable conditions for urbanization and migration from low- to high-latitude countries. Encompassing slow- and fast-onset mechanisms, our projections suggest that climate change will induce the voluntary and forced displacement of 100 to 160 million workers (200 to 300 million climate migrants of all ages) over the course of the 21st century. However, under current migration laws and policies, forcibly displaced people predominantly relocate within their country and merely 20% of climate migrants opt for long-haul migration to OECD countries. If climate change induces generalized and persistent conflicts over resources in regions at risk, we project significantly larger cross-border flows in the future.
Keywords: E24; F22; J24; J61; O15; Q54; 330; climate change; migration; inequality; urbanization; conflicts